Sustaining Wildlands : Integrating Science and Community in Prince William Sound - Poe, Aaron J. (Book collections on Project MUSE., 2017)
"Nearly thirty years after the Exxon Valdez oil spill, land managers and stakeholders explore the ongoing paradox of accommodating human use while reducing environmental impact in Prince William Sound"--Provided by publisher